Revisiting Public-Private Partnerships in the Power Sector - Vagliasindi, Maria (Washington, DC: World Bank, 2013)
As the world demand for energy continues to grow, a big question is where will all the energy come from and what will the price tag be. With such enormous sums needed, public-private partnerships (PPPs) could play a big role. But the financial crisis has raised worries about funding, and much is still not known about how best to attract PPPs. This report reviews the evidence to date with sectoral reforms and considers different approaches in varying circumstances to help outline the potential role of the private and public sector in: 1) strengthening the corporate governance of private and public utilities; 2) helping governments to establish legal, regulatory, contractual, and fiscal frameworks; and 3) improved market governance to attract private investment. Chapter one reviews the impact of the recent financial crisis on PPP investment compared with what happened in earlier financial crises. It also looks out the latest projections for additional power sector investment needed because of climate change and the possible sources of financing. Chapter two examines how PPP investment in the power sector has fared. It also gives the results of an econometric study that explores which types of incentives and variables matter most to PPPs when they are weighing entering the power sector, especially in renewables, and what influences the ongoing level of investment. The idea is to provide a powerful benchmarking tool at the sector and country levels against which governments and policy makers can evaluate progress on this issue. Chapter three examines four case studies-in China, Brazil, Peru, and Mexico-to identify, disseminate, and promote best practices on alternative ways to attract PPPs.